Pendidikan Islam Pada Era Kemunduran Pasca Kejatuhan Bagdad Dan Cordova - Dr. Komaruddin Sassi (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2019)
The golden age experienced by the Islamic world in the classicaal era brought lesson as well as fresh air for forerunner to the growthand development of Western civilization in various aspects including education. In fact, it has become the driving force of the West in realizing the shortcomings and deterioration that it has experienced. On the contrary, the humiliation and chaos of the conflict in the Daulah Islamiyah body that continued to rage in that era, frustrated the permanence of Islamic education. Especially after the fall of Bagdad and Cordova.